2011
DOI: 10.1088/0034-4885/74/6/066701
|View full text |Cite
|
Sign up to set email alerts
|

Solar radiation and human health

Abstract: The Sun has played a major role in the development of life on Earth. In Western culture, people are warned against Sun exposure because of its adverse effects: erythema, photoimmunosuppression, photoageing, photocarcinogenesis, cataracts and photokeratitis. However, Sun exposure is also beneficial, since moderate doses give beneficial physiological effects: vitamin D synthesis, reduction of blood pressure and mental health. Shortage of Sun exposure may be even more dangerous to human health than excessive expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
119
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 506 publications
(582 reference statements)
0
119
0
8
Order By: Relevance
“…Hourly SSI is the irradiation received during one hour. The SSI plays a major role in many domains such as weather and climate (Abdel Wahab et al, 2009;Blanc et al, 2011Blanc et al, , 2015Lefèvre et al, 2007), ocean (Bell et al, 2009), agriculture (Bois et al, 2008a), forestry (Colombo et al, 2009), ecology (Wagner et al, 2011), oenology (Bois et al, 2008b), human health (Juzeniene et al, 2011), energy (Kenfack et al, 2009;Szabó et al, 2011), or architecture (Leloux et al, 2012;Rotar and Badescu, 2011). Current means for SSI assessment are ground-based instruments which may offer high to good quality measurements if well attended but are too few to offer the coverage needed in space and time.…”
Section: Introductionmentioning
confidence: 99%
“…Hourly SSI is the irradiation received during one hour. The SSI plays a major role in many domains such as weather and climate (Abdel Wahab et al, 2009;Blanc et al, 2011Blanc et al, , 2015Lefèvre et al, 2007), ocean (Bell et al, 2009), agriculture (Bois et al, 2008a), forestry (Colombo et al, 2009), ecology (Wagner et al, 2011), oenology (Bois et al, 2008b), human health (Juzeniene et al, 2011), energy (Kenfack et al, 2009;Szabó et al, 2011), or architecture (Leloux et al, 2012;Rotar and Badescu, 2011). Current means for SSI assessment are ground-based instruments which may offer high to good quality measurements if well attended but are too few to offer the coverage needed in space and time.…”
Section: Introductionmentioning
confidence: 99%
“…Although ultraviolet (UV) radiation is only a small fraction (< 10 %) of the total solar radiation that reaches the Earth's surface, it is vital for the life on Earth (Asta et al, 2011;Häder et al, 2015;Lucas et al, 2015;UNEP, 2010;Williamson et al, 2014). The amount of solar UV radiation reaching the atmosphere is changing periodically due to changes in the Earth-Sun distance and the solar activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, small amounts of UV radiation have beneficial effects since they stimulate the production of vitamin D in the human body. In addition several recent studies suggested the possible protective role of vitamin D in some neoplasias of internal organs [1]. The latitude extension and the variety of environmental conditions of the Mediterranean as well as of the Alpine regions make solar UV measurements an important issue in Italy [2] where, however, a climatological characterization of biologically effective UV radiation is still missing.…”
Section: Introductionmentioning
confidence: 99%